Stochastic Optimal Dispatch of Integrated Energy Campus Microgrids Considering the Time-Delay of Pipelines - Liang, Weikun; Lin, Shunjiang; Sheng, Xuan; Tang, Zhiqiang (2021 IEEE 5th Conference on Energy Internet and Energy System Integration (EI2), 2021)
A stochastic optimal dispatch model for integrated energy campus microgrid (IECM) is proposed, which considered the stochastic fluctuation of photovoltaic and photothermal power outputs and the time-delay of energy transmission in cooling/heating and gas pipelines. The orthogonal collocation on finite elements in the two-dimensional domain was used to transform the partial differential equations describing the dynamic of pipelines into algebraic equations. The State-space approximate dynamic programming (SS-ADP) algorithm is adopted to solve the stochastic optimal dispatch model. Firstly, typical state spaces are generated by solving deterministic optimal dispatch models in a series of stochastic scenarios. Secondly, approximate value function (AVF) of each typical state is obtained based on the transition probability matrix of random variables and the similarity index. Finally, by the forecast scenario of random variables, the optimal dispatch solution can be obtained by solving each time period's optimal model successively based on the AVFs of typical states. Test results on an IECM demonstrate the correctness and efficiency of the proposed model and algorithm.